Clinical utiliy of serum lactate levels in diabetic ketoacidosis in adult patients admitted to emergency department (Annals of Medical Research, 2022)
Aim: To evaluate serum lactate and its clinical utility for disease severity among patients admitted to the emergency department with diabetic ketoacidosis (DKA) diagnosis.Materials and Methods: This is a retrospective data review that included patients 18 years of age and admitted to the department with a DKA diagnosis. Patients with a blood glucose level of 250 mg/dL between 01 January 2016 to 30 June 2021 with DKA were included. Patients without arterial blood gas or urine ketone analyses or diagnosed with isolated hyperglycemia were excluded. DKA was defined as a blood glucose level 250 mg/dL, pH
Keywords: Lactate; Diabetic ketoacidosis; Metabolic acidosis; Biomarker; Emergency department